The effects of prebiotics on gastrointestinal side effects of metformin in youth: A pilot randomized control trial in youth-onset type 2 diabetes - Dixon, Sydney A.; Mishra, Sidharth; Dietsche, Katrina B.; Jain, Shalini; Mabundo, Lilian; Stagliano, Michael; Krenek, Andrea; Courville, Amber; Yang, Shanna; Turner, Sara A.; Meyers, Abby G.; Estrada, Doris E.; et al. (Frontiers in Endocrinology, 2023)
Disclosure summary Dr. Yadav is Chief Scientific Officer and Co-Founder of Postbiotics Inc and has no conflict of interest with this work. All other authors have no conflicts of interest to disclose. Background Metformin is the only approved first-line oral glucose lowering agent for youth with type 2 diabetes mellitus (Y-T2DM) but often causes gastrointestinal (GI) side effects, which may contribute to reduced treatment adherence and efficacy. Prebiotic intake may reduce metformin’s side effects by shifting microbiota composition and activity. Objective The aims of this study were to determine the feasibility and tolerability of a prebiotic supplement to improve metformin-induced GI symptoms and explore the changes in glycemia and shifts in the microbiota diversity. Methods In a two-phase pilot clinical trial, we compared, stool frequency and stool form every 1-2 days, and composite lower GI symptoms (weekly) at initiation of daily metformin combined with either a daily prebiotic or a placebo shake in a 1-week randomized double-blind crossover design (Phase 1), followed by a 1-month open-labeled extension (Phase 2). Plasma glycemic markers and stool samples were collected before and after each phase. Results Six Y-T2DM (17.2 ± 1.7y (mean ± SD), 67% male, BMI (42 ± 9 kg/m2), HbA1c (6.4 ± 0.6%)) completed the intervention. Stool frequency, stool composition, and GI symptom scores did not differ by group or study phase. There were no serious or severe adverse events reported, and no differences in metabolic or glycemic markers. After one week Phase 1metformin/placebo Proteobacteria, Enterobacteriaceae, and Enterobacteriales were identified as candidate biomarkers of metformin effects. Principle coordinate analyses of beta diversity suggested that the metformin/prebiotic intervention was associated with distinct shifts in the microbiome signatures at one week and one month. Conclusion Administration of a prebiotic fiber supplement during short-term metformin therapy was well tolerated in Y-T2DM and associated with modest shifts in microbial composition. This study provides a proof-of-concept for feasibility exploring prebiotic-metformin-microbiome interactions as a basis for adjunctive metformin therapy. Clinical trial registration https://clinicaltrials.gov/, identifier NCT04209075.